EFFECT OF SEX DIFFERENCE ON THE HISTOLOGICAL STRUCTURE OF BRONCHUS AND NASAL CAVITY IN ANIMAL ASTHMA MODEL - Reinaldi Rachmadhianto; Tri Hartini Yuliawati; Gatot Soegiarto (Majalah Biomorfologi, 2020)
Background: The prevalence of asthma in prepuberty women is more common than in puberty men. Even after puberty, to a certain age, women dominate more. It is still unclear whether sex hormones affect the histological structure of male and female airways. Objective: This study objective was to examine the effect of sex difference on the histological structure of bronchial and nasal cavity of mice model (Mus musculus) with ovalbumin exposure. Materials and Methods: This study used 24 mice in four groups (male control, female control, male asthma model, and female asthma model). At the sensitization phase in days 0 and 14, the mice were injected intraperitoneally with 100 μl of a mixture of 50 μl ovalbumin (200 μl/ml) and 50 μl alum. At the exposure phase in days 21 to 23, the mice were exposed to 1% ovalbumin (aerosol, 30 minutes/per day). The mice were sacrificed 48 hours after the last exposure. The data taken included four variables, bronchial epithelial thickness, bronchial smooth muscle thickness, nasal cavity goblet cells number, and nasal cavity mucosal thickness. Then, Shapiro-Wilk normality test and parametric t-test were conducted. Results: In animal asthma models, mice with male and female exposure did not cause differences in epithelial thickness and smooth muscle thickness in bronchus compared to the control group. However, there were significant differences in the number of goblet cells and mucosal thickness in nasal cavity of male and female mice compared to the control group (respectively, p= 0.002; p= 0.006 and p= 0.003; p = 0.005). There were no significant differences between groups of male and female mice on all variables. Conclusion: In animal asthma models of mice, ovalbumin exposure did not cause differences in the values of all variables between male and female groups.